Expression of chickpea CIPK25 enhances root growth and tolerance to dehydration and salt stress in transgenic tobacco - Meena, Mukesh K.; Ghawana, Sanjay; Dwivedi, Vikas; Roy, Ansuman; Chattopadhyay, Debasis (Frontiers in Plant Science, 2015)
Calcium signaling plays an important role in adaptation and developmental processes in plants and animals. A class of calcium sensors, known as Calcineurin B-like (CBL) proteins sense specific temporal changes in cytosolic Ca2+ concentration and regulate activities of a group of ser/thr protein kinases called CBL-interacting protein kinases (CIPKs). Although a number of CIPKs have been shown to play crucial roles in the regulation of stress signaling, no study on the function of CIPK25 or its orthologues has been reported so far. In the present study, an orthologue of Arabidopsis CIPK25 was cloned from chickpea (Cicer arietinum). CaCIPK25 gene expression in chickpea increased upon salt, dehydration, and different hormonal treatments. CaCIPK25 gene showed differential tissue-specific expression. 5'-upstream activation sequence (5'-UAS) of the gene and its different truncated versions were fused to a reporter gene and studied in Arabidopsis to identify promoter regions directing its tissue-specific expression. Replacement of a conserved threonine residue with an aspartic acid at its catalytic site increased the kinase activity of CaCIPK25 by 2.5-fold. Transgenic tobacco plants overexpressing full-length and the high active versions of CaCIPK25 displayed a differential germination period and longer root length in comparison to the control plants. Expression of CaCIPK25 and its high active form differentially increased salt and water-deficit tolerance demonstrated by improved growth and reduced leaf chlorosis suggesting that the kinase activity of CaCIPK25 was required for these functions. Expressions of the abiotic stress marker genes were enhanced in the CaCIPK25-expressing tobacco plants. Our results suggested that CaCIPK25 functions in root development and abiotic stress tolerance.